How do you spell g*e*e*k? - Peters, Julie Anne. (New York ; Boston : Little, Brown, 2009)
When Ann is assigned to sponsor new student Lurlene, who is an excellent speller, it threatens her relationship with best friend Kimberly and their chances of competing in the National Spelling Bee in Washington, D.C.
570
Keywords: Spelling bees -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction